Air pollution dispersion models validation dataset from complex terrain in Šoštanj. (2015) - Mlakar, PrimoÅ¾; BoÅ¾nar, Marija Zlata; GraÅ¡iÄ, BoÅ¡tjan; Brusasca, Giuseppe; Tinarelli, Gianni; Morselli, Maria Grazia; Finardi, Sandro
In 1991, three institutions from Slovenia and Italy performed a measuring campaign to collect data for the validation of air pollution dispersion models. The target was a local area around the Šoštanj Thermal Power Plant in north-east Slovenia. As one of the co-authors of the work we decided to renew the database and to produce the necessary up-to-date information that would allow other researchers to use this experimental database for modern models testing. The measurements data set describes in detail the following situation: Šoštanj Thermal Power Plant at that time did not have any desulphurisation plants, therefore the sulphur dioxide (SO2 ) continuously emitted from its blocks was acting like a tracer in the environment. The area is characterised by very complex meteorological situations. In the paper we will present a description of the experiment (area description, site, terrain, measurement stations location, database) and two most interesting cases suitable for a model validation (emission, ambient concentrations, meteorology).